Pembuatan tepung porang sebagai upaya peningkatan penjualan umbi porang di masa pandemi covid19 - Yuniwati, Ika; Pamuji, Dian Ridlo; Trianasari, Ely; Rahayu, Ninik Sri; Ulfiyati, Yuni (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
Food sales during the Covid19 pandemic experienced a decline. This also includes Umbi Porang. Kembiritan Village Farmers Group, Genteng District, Banyuwangi Regency is one of the areas in Banyuwangi that produces porang tubers. To solve this sales problem, it is necessary to improve the quality of porang tuber sales by processing porang tubers into the desired shape by consumers. However, the Kembiritan Village Farmer Group cannot process porang tubers into porang flour due to several problems, namely they do not have a machine capable of pounding dry porang chips into porang flour and do not have human resources who can operate machines. Based on these problems, it is necessary to develop a porang tuber-making machine and Human Resources training from partners. This community service began with adjusting the porang tuber-making machine according to the porang tuber at the partner's place. After adjustments were made, training was carried out on the use of the porang flour making machine and the maintenance of the porang tuber-making machine. Then, partner assistance is carried out in determining the quality of porang tuber sales. Where the quality is determined from the capacity per transport of various forms of porang tubers.